An Approach to Differential Diagnosis of Antiphospholipid Antibody Syndrome and Related Conditions - Giacomo Emmi; Elena Silvestri; Danilo Squatrito; Lucia Ciucciarelli; Anna Maria Cameli; Gentian Denas; Mario Milco D’Elios; Vittorio Pengo; Lorenzo Emmi; Domenico Prisco (The Scientific World Journal)
The antiphospholipid antibody syndrome is a systemic, acquired, immune-mediated disorder characterized by episodes of venous, arterial, or microcirculation thrombosis and/or pregnancy abnormalities, associated with the persistent presence of autoantibodies, confirmed at least in two occasions 12 weeks apart, directed to molecular complexes consisting of phospholipids and proteins. Antiphospholipid antibody syndrome should always be considered as a potential diagnosis especially for young patients presenting with a history of thrombotic events, in particular when they occur without any obvious external trigger or any inherited thrombophilic mutation (even if 2006 criteria do not exclude antiphospholipid antibody syndrome in patients with other inherited or acquired prothrombotic conditions), or for women with recurrent pregnancy losses or later fetal deaths. Many other disorders are able to mimic antiphospholipid antibody syndrome, so a broad range of alternative diagnoses should be investigated and ruled out during clinical workup.